SYSTEMIC TOXICITY FROM TOPICALLY APPLIED VIRGIN COCONUT OIL IN BURNED EXPERIMENTAL ANIMALS - Nguyen, Thi Thanh Loan (Tạp chí Sinh lý học Việt Nam, 2024)
The healing properties and potential benefits of virgin coconut oil (VCO) for treating burned skin lesions have been demonstrated. Nevertheless, prolonged topical use can lead to systemic effects, especially when applied to open wounds. Currently, the systemic toxicity of topical VCO in burned experimental animals has yet to be fully elucidated. Objective: The present study investigated the systemic toxicity from topically applied VCO in burned experimental animals. Methods: All animals, except the normal control group, were subjected to thermal burns on the back of each rat by using a standard burning technique. Following the burning, each animal was placed in a separate cage, and the affected areas were covered with VCO 0.2 or 0.4 ml/day twice a day for 21 consecutive days. Hematological and biochemical analyses were determined. Macroscopic and histopathological examinations of the liver and kidney were conducted at the end of the treatment period. Results: Our results indicated that topical administration of VCO caused no significant change in animals’ general status, hematological parameters, and renal and hepatic functions. Additionally, it did not alter the liver and kidney histology in animals. Conclusion: These findings suggest that the topical application of VCO was considered safe for the wounded animals.